Pengembangan Kelompok Usahatani Berbasis HHBK Minyak Atsiri di Pulau Hiri - Marasabessy, Much Hidayah; Baguna, Firlawanti Lestari; Kurniawan, Andy; Sabaruddin B. (Program Studi Kehutanan, Universitas Khairun, 2024)
The use of Clove and Lemongrass NTFPs as essential oils by the Manyeku Book Forest Farmers Group on Hiri Island opens up business opportunities to increase farmers' income. The activity time is May 2024. Community Service Activities (PKM) are carried out in the Socialization and Essential Oil Refining Demonstration Stage. Community service activities can provide information to the community, especially farmer groups, to cultivate non-timber forest products as a source of livelihood. Activities carried out in the form of outreach and training have increased the insight and skills of farmer groups regarding raw materials and factors that influence the quality of essential oils in the production process to give information material in developing farming businesses. Keywords: Cengkeh, Essential Oil, Farming Groups, Hiri Isle, NTFPs